Teaching style and student well-being: regression analysis in Filipino language learning - Ma. Ernalyn B. Cepeda; Jonalyn L. Denusta; Salvador P. Bacio Jr. (International Journal of Evaluation and Research in Education (IJERE), 2026)
Teaching style is widely theorized to shape learners’ affective experiences in language classrooms, yet empirical evidence remains limited in Filipino language settings, an underexplored context compared with the extensive English-focused literature. This study examined the extent to which teaching-style dimensions influence students’ anxiety, motivation, and attitudes toward Filipino. Using a descriptive-correlational design with multiple regression analysis, data were collected from 120 Grades 7–10 students enrolled in the Integrated Laboratory School (ILS) of a state university. Three validated instruments were employed: a Filipino-adapted foreign language classroom anxiety scale (FLCAS), the attitude and motivation test battery, and a teaching-style inventory assessing authority, managerial, delegator, facilitator, and hybrid dimensions. Findings showed high levels of anxiety, motivation, and attitudes toward Filipino. Teaching style dimensions were positively associated with motivation and attitudes, but not with anxiety. Regression results further indicated that only the hybrid teaching style significantly predicted students’ attitudes, whereas no teaching-style dimension significantly predicted anxiety or motivation. These results provide context-sensitive evidence for Philippine multilingual classrooms, highlighting the practical value of hybrid teaching in strengthening positive attitudes while indicating that anxiety likely requires targeted interventions beyond teaching style alone.